2017
DOI: 10.1039/c7sc03351f
|View full text |Cite|
|
Sign up to set email alerts
|

Self-quenched ferrocenyl diketopyrrolopyrrole organic nanoparticles with amplifying photothermal effect for cancer therapy

Abstract: A NIR D–A–D structure of a ferrocene flanked diketopyrrolopyrrole derivative with a tetracyanobutadiene unit is synthesized for photoacoustic imaging-guided amplifying photothermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…Photodynamic therapy (PDT) and photothermal therapy (PTT) have now been considered as novel alternatives to traditional oncology treatments with high selectivity, low toxicity, no drug resistance and lower non-invasiveness. 5 13 PDT and PTT depend on photon energy absorbed by photosensitizers to generate reactive oxygen species (ROS) or heat, causing damage or death of blood vessels and tumor cells. 14 – 18 Owing to the difference of pH value between the tumor microenvironment (pH 4.5–5.0) and normal tissues (pH 7.4), 19 22 smart pH-activated photosensitizers are extremely desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) and photothermal therapy (PTT) have now been considered as novel alternatives to traditional oncology treatments with high selectivity, low toxicity, no drug resistance and lower non-invasiveness. 5 13 PDT and PTT depend on photon energy absorbed by photosensitizers to generate reactive oxygen species (ROS) or heat, causing damage or death of blood vessels and tumor cells. 14 – 18 Owing to the difference of pH value between the tumor microenvironment (pH 4.5–5.0) and normal tissues (pH 7.4), 19 22 smart pH-activated photosensitizers are extremely desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al . showed that the diketopyrrolopyrrole derivative (DPPCN‐Fc) irradiated by a laser for 10 min showed 59.1% photothermal conversion, which is higher than the rates of most reported photothermal therapeutic agents …”
Section: Resultsmentioning
confidence: 99%
“…It is found that the temperature change of TA1 NPs is dependent on both laser irradiation time and NP concentration. Notably, while the temperature of PBS remained almost constant under the same conditions, the temperature of TA1 NP suspension (50 µg mL −1 ) rapidly increased to 65.8 °C after 5 min of irradiation with a PCE of 84.8% (Supporting Information), which is much higher than terrylenediimide derivatives (41%), BODIPY derivatives (26.0%), ferrocenyl diketopyrrolopyrrole (59.1%), 2TPE‐2NDTA‐doped NPs (27.5%), and NIRb10 (29.8%) . Since PTT agents are often used for repeated or long‐term therapeutic treatment under NIR laser irradiation, the photothermal stability of TA1 NPs were studied in vitro with ICG as comparison (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…While CPs generally show molecular polydispersity with low reproducibility, small organic PTT agents could overcome these shortcomings . However, conventional small organic PTT agents face some challenges, such as low photostability for porphyrins and indocyanine green (ICG), limited photothermal conversion efficiency (PCE) for most terrylenediimide and BODIPY derivatives, and low extinction coefficient for diketopyrrolopyrrole derivatives . Recently, organic molecules with propeller structures, like BTPETTQ, 2TPE‐2NDTA, and NR6, have shown promising PTT applications .…”
Section: Introductionmentioning
confidence: 99%